2006
DOI: 10.1063/1.2204049
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence characteristics of the Bödewadt layer in a large enclosed rotor-stator system

Abstract: A three-dimensional direct numerical simulation (3D DNS) is combined with a laboratory study to describe the turbulent flow in an enclosed annular rotor-stator cavity characterized by a large aspect ratio G = (b − a)/h = 18.32 and a small radius ratio a/b = 0.152, where a and b are the inner and outer radii of the rotating disk and h is the interdisk spacing. The rotation rate Ω under consideration is equivalent to the rotational Reynolds number Re = Ωb 2 /ν = 9.5× 10 4 , where ν is the kinematic viscosity of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…On the rotor side, the fluid is arriving from smaller radii where the flow is laminar, while on the stator side, the fluid comes from larger radii where turbulence prevails. The low value of the maximum of the turbulent Reynolds number Re t = k 2 /(ν ) = 20.52 [5] confirms the weakly turbulent nature of this flow, to be compared with the value Re t = 352 obtained by Poncet et al [3] at Re = 10 6 with G = 23.89. Although the profiles from the simulation resemble the behavior obtained from velocity measurements for R * rr and R * θθ until r * = 0.68, the Direct Numerical Simulation (DNS) underestimates these two normal components towards the periphery of the cavity.…”
Section: Turbulence Fieldsupporting
confidence: 61%
See 1 more Smart Citation
“…On the rotor side, the fluid is arriving from smaller radii where the flow is laminar, while on the stator side, the fluid comes from larger radii where turbulence prevails. The low value of the maximum of the turbulent Reynolds number Re t = k 2 /(ν ) = 20.52 [5] confirms the weakly turbulent nature of this flow, to be compared with the value Re t = 352 obtained by Poncet et al [3] at Re = 10 6 with G = 23.89. Although the profiles from the simulation resemble the behavior obtained from velocity measurements for R * rr and R * θθ until r * = 0.68, the Direct Numerical Simulation (DNS) underestimates these two normal components towards the periphery of the cavity.…”
Section: Turbulence Fieldsupporting
confidence: 61%
“…They have simulated the fully turbulent flow in an infinite two-disk configuration and provided a detailed set of data to analyse the near-wall coherent structures [1]. The reader is referred to the work of Randriamampianina and Poncet [5] for a detailed review on both rotating disk flows and three-dimensional turbulent boundary layers (3DTBLs).…”
Section: Introductionmentioning
confidence: 99%
“…This related problem consists of a rotating disk and a stationary disk, shrouded by a cylindrical sidewall, and there may also be an inner cylindrical hub. [37][38][39][40][41][42] However, the motivation for these studies comes from applications in turbomachinery rather than interests in crossflow boundary layer instabilities, and the setups studied typically have the gap between the two disks being a very small fraction of their radius and the cylindrical shroud is stationary. These characteristics of the rotor-stator setup lead to the boundary layer on the rotating disk being turned into the interior by the presence of the stationary shroud, forming a free shear layer that under some conditions becomes unstable to azimuthal waves 43 or the free shear layer may be drawn ͑via Ekman suction type processes͒ into either the boundary layer on the rotating or stationary disk or even periodically flipping between the two.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that their study indicated that the features of 3DTBLs depend on the flow configuration in question. In two very recent studies, Randriamampianina and Poncet [21] and Poncet and Randriamampianina [22] performed an experimental and numerical (DNS) investigation of turbulence characteristics in an enclosed rotor-stator system. The typical reduction in the structure parameter and the non-alignment of the velocity gradient and turbulent shear stress angles were observed.…”
Section: Introductionmentioning
confidence: 99%